2017
DOI: 10.1002/cvj.12059
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Forgiveness Buffer Distress: Associations With Interpersonal Transgression Blameworthiness

Abstract: This study examined psychopathological symptom outcomes in victims of interpersonal transgressions (IPTs) based on differences in offender blameworthiness attributions. Mindfulness and forgiveness were hypothesized to serve as protective factors against depression, anxiety, and stress symptoms. The results highlight the buffering influence of dispositional mindfulness and forgiveness on symptoms of depression, anxiety, and stress. These results provide initial evidence that mindfulness‐ and forgiveness‐based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Discussing and forgiving relational hurt leads to increased intimacy and relationship satisfaction (Fincham & Beach, 2003). Mindfulness is associated with interpersonal forgiveness (e.g., Jarrett, Pickett, Amsbaugh, & Afzal, 2017; Karremans et al, 2020), and appears to be a skill that may enable couples to effectively engage in these discussions of relational hurt.…”
Section: Discussionmentioning
confidence: 99%
“…Discussing and forgiving relational hurt leads to increased intimacy and relationship satisfaction (Fincham & Beach, 2003). Mindfulness is associated with interpersonal forgiveness (e.g., Jarrett, Pickett, Amsbaugh, & Afzal, 2017; Karremans et al, 2020), and appears to be a skill that may enable couples to effectively engage in these discussions of relational hurt.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that IF played a protective role in the relationship between CV and PBJW. Many previous studies have supported the buffer role of IF against adverse experiences (Hirsch et al, 2012;Jarrett et al, 2017;Quintana-Orts & Rey, 2018). A possible explanation is that the victim's expression of forgiveness toward the cyberbullying perpetrators seemed to empower the victim and increase their perceived status, and in turn, this sense of status/ power alleviated the victim's feelings of injustice (Wenzel & Okimoto, 2012).…”
Section: Np19636mentioning
confidence: 92%
“…There is substantial evidence that mindfulness-oriented clinical interventions and mindfulness-based meditation practices can improve interpersonal functioning (Abbass et al, 2014;Keng et al, 2011;Sedlmeier et al, 2012). Enhanced dispositional mindfulness resulting from mindfulness-oriented interventions is also associated with a range of beneficial VIPASSANA EFFECTS ON PSYCHOLOGICAL FUNCTIONING interpersonal outcomes, including enhanced interpersonal well-being amongst students (Sawyer Cohen & Miller, 2009), increased perspective-taking and awareness of one's own needs, resulting in better quality friendships (Pratscher, Rose, Markovitz, & Bettencourt, 2017), a greater propensity for forgiveness against interpersonal transgressions (Jarrett, Pickett, Amsbaugh, & Afzal, 2017), increased perceptions of social connectedness (Kok & Singer, 2017), and reductions in interpersonal sensitivity (Kliem, Kröger, & Kosfelder, 2010).…”
Section: Dispositional Mindfulness and Interpersonal Functioningmentioning
confidence: 99%